2021
DOI: 10.1101/2021.04.13.439465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifunctional RNA-binding proteins influence mRNA abundance and translational efficiency of distinct sets of target genes

Abstract: RNA-binding proteins (RBPs) are key regulators of RNA metabolism. Many RBPs possess uncharacterized RNA-binding domains and localize to multiple subcellular compartments, suggesting their involvement in multiple biological processes. We searched for such multifunctionality within a set of 143 RBPs by integrating experimentally validated target genes with the transcriptomes and translatomes of 80 human hearts. This revealed that RBP abundance is predictive of the extent of target regulation in vivo, leading us … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
(195 reference statements)
1
3
0
Order By: Relevance
“…The co-mRNA transfection data in Figure 3C show that in situ competition in the translation of Spike and Nuc mRNAs, are consistent with previous studies showing that endogenous cellular RNAs compete with each other for resources used in translation including association with RNA binding proteins that are integral to the process of translation (Asselbergs et al, 1978;Godefroy-Colburn and Thach, 1981;Jain et al, 2022;Ray et al, 1983;Schneider-Lunitz et al, 2021). Studies have further shown that SARS-CoV-2 infection results in reduced translation of host-cell mRNAs that have a preponderance of the same codons that are enriched in SARS-CoV-2 (Alonso and Diambra, 2020) also known as epistasis (Mogro et al, 2022;Fumagalli et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…The co-mRNA transfection data in Figure 3C show that in situ competition in the translation of Spike and Nuc mRNAs, are consistent with previous studies showing that endogenous cellular RNAs compete with each other for resources used in translation including association with RNA binding proteins that are integral to the process of translation (Asselbergs et al, 1978;Godefroy-Colburn and Thach, 1981;Jain et al, 2022;Ray et al, 1983;Schneider-Lunitz et al, 2021). Studies have further shown that SARS-CoV-2 infection results in reduced translation of host-cell mRNAs that have a preponderance of the same codons that are enriched in SARS-CoV-2 (Alonso and Diambra, 2020) also known as epistasis (Mogro et al, 2022;Fumagalli et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…The described examples of stability regulation achieved via CDS binding are so far sparse and seem to be well-connected to the regulation of translation, which is in line with the above reasoning. In fact, dual regulatory effects of the same RBPs, impacting both mRNA stability and translation rates, have been postulated for some RBPs [ 19 ]. The two functionalities seem to be intertwined also in the case of CDS-binding RBPs.…”
Section: Functionality Of Cds Bindingmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 23, 2022. ; https://doi.org/10.1101/2022.10.23.513405 doi: bioRxiv preprint 2017; Mo et al, 2021;Schneider-Lunitz et al, 2021). DDX3 overexpression has been implicated in many diseases including viral infections, inflammatory autoimmune diseases, and many forms of cancer (Bol et al, 2015;Kukhanova et al, 2020;Tantravedi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…RNA binding proteins (RBPs) are capable of regulating translation for the rapid modulation of protein synthesis from the existing mRNA (Hentze et al, 2018). RBPs can either sequester mRNA to slow translation, such as the P-body proteins AGO2 and UPF1; promote translation, such as DDX3, or actively suppress and degrade mRNA, such as CELF2 (Hubstenberger et al, 2017; Mo et al, 2021; Schneider-Lunitz et al, 2021). DDX3 overexpression has been implicated in many diseases including viral infections, inflammatory autoimmune diseases, and many forms of cancer (Bol et al, 2015; Kukhanova et al, 2020; Tantravedi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%